ANALISIS PERAN BUDAYA KEKERABATAN DAN PERILAKU ETIS DALAM KAITANNYA DENGAN INDEPENDENSI AUDITOR PADA KANTOR INSPEKTORAT KOTA KENDARI - Hasbudin, Hasbudin; Dharmawati, Tuti; Aspar, Zulkifli (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
This study aims to exam the role of cultural kinship and ethical behavior in relation to the independence of auditors. Kinship cultural indicators used in this study is the attitude of individualism and collectivism while ethical behavior used in this study is more directed at the attitudes and behavior in the performance of auditors.The population in this study amounted to 28 people consisting of PPUPD totaling 14 people and Auditor totaling 14 people in the Office of the Inspectorate of Kendari. A total of 28 samples were obtained using census method. In analyzing the role of the independent and dependent variables used descriptive analysisResearch shows that the role of cultural kinship and ethical behavior in relation to the independence of the auditor have a role in the independence of auditors, whose attitude is more likely to maintain independence individualism than collectivism attitudes, views of auditors tend to use the attitude of individualism or collectivism in every pemeriksaanya. And ethical behavior that is well understood by auditors not hamper the independence but it is able to maintain the independence of the auditor itself. Keywords: Kinship Cultural, Ethical Behavior, Auditor Independence.